2015
DOI: 10.3109/14767058.2015.1038232
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes of feeding low birth weight infants with predominantly raw human milk versus donor banked milk and formula

Abstract: Feeding predominantly with mother's raw milk seems to result in optimal neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 47 publications
2
80
0
4
Order By: Relevance
“…Though, there is an ongoing number of studies that support the opposite view. These studies have shown that, when preterm raw or donor banked milk is either targeted fortified or under adjustable fortification (individualized fortification), is capable of inducing improved short-term outcomes on neonatal somatometric characteristics, as compared with feeding mainly with a preterm formula [14,16,17] . In our recently conducted study (Dritsakou K., Liosis G. et al, 2015), infants fed mainly with a preterm formula presented smaller somatometric characteristics, at hospital discharge, when compared to those infants that were fed with targeted fortified human milk.…”
Section: Human Milk Banking Establishment and Exclusive Breastfeedingmentioning
confidence: 99%
See 4 more Smart Citations
“…Though, there is an ongoing number of studies that support the opposite view. These studies have shown that, when preterm raw or donor banked milk is either targeted fortified or under adjustable fortification (individualized fortification), is capable of inducing improved short-term outcomes on neonatal somatometric characteristics, as compared with feeding mainly with a preterm formula [14,16,17] . In our recently conducted study (Dritsakou K., Liosis G. et al, 2015), infants fed mainly with a preterm formula presented smaller somatometric characteristics, at hospital discharge, when compared to those infants that were fed with targeted fortified human milk.…”
Section: Human Milk Banking Establishment and Exclusive Breastfeedingmentioning
confidence: 99%
“…In our recently conducted study (Dritsakou K., Liosis G. et al, 2015), infants fed mainly with a preterm formula presented smaller somatometric characteristics, at hospital discharge, when compared to those infants that were fed with targeted fortified human milk. It is remarkable that preterm infants fed with the absolute human milk diet, that is targeted fortified, regain earlier their birth weight and present fewer episodes of feeding intolerance [16] . It is obvious that by including the, necessary for a proper growth, hormones, the macronutrients and micronutrients, the growth factors and all the other elements that are necessary for development, human breast milk is thought as the most complete food for the earliest stages of life.…”
Section: Human Milk Banking Establishment and Exclusive Breastfeedingmentioning
confidence: 99%
See 3 more Smart Citations